A influência de vieses cognitivos nas tomadas de decisões no setor público - Campos, Guilherme Freitas (2025)
The decision-making process in the public sector plays a crucial role in public administration, directly impacting efficiency, equity, and social well-being. However, decisions in this context are not always rational, as they can be influenced by cognitive biases, potentially leading to negative outcomes such as inefficient resource allocation, inadequate public policy implementation, and the erosion of public trust in government officials. Biases such as anchoring, sunk costs, overconfidence, availability, free effect, ownership effect, and status quo bias can distort judgment and compromise the quality of decisions. The main objective of this study is to analyze how public servants perceive and understand the influence of cognitive biases in decision-making and how they manage these factors. It also seeks to explore possible strategies to mitigate biases when they may be harmful. Theoretically, the research is based on literature related to Prospect Theory and Behavioral Economics, focusing on cognitive biases and their practical implications, supported by a systematic literature review on the topic. Regarding methods and procedures, semi-structured interviews were conducted with public servants holding or substituting for leadership positions or receiving additional compensation for special duties, with the Federal University of Espírito Santo as the research locus. The collected data were analyzed using content analysis in three stages: pre-analysis, material exploration, and results processing. Responses were categorized based on the interviewees’ level of understanding of cognitive biases, classified into null, vague, partial, and complete comprehension, according to indicators of clarity, depth, and connection with the core concept. The findings highlight that managers generally lack prior knowledge of cognitive biases, both broadly and specifically. However, when introduced to these concepts, they demonstrated comprehension, indicating that many public managers have only a limited understanding of biases and their implications for their daily routines and decision-making processes. In conclusion, certain cognitive biases, such as status quo bias, free effect, overconfidence, and ownership effect, seem to be more easily understood by public servants, suggesting a correlation with the nature of the public sector. Together with the tools identified by managers, the study suggests practices to reduce the influence of cognitive biases. As a technical product, an educational material was developed with practical guidelines and strategies focused on mitigating cognitive biases in the public sector. The purpose of this material is to provide recommendations and guidelines for implementing these strategies in decision-making processes, aiming to promote a more efficient and informed public administration